10Be Indicator for the Matuyama‐Gauss Magnetic Polarity Reversal From Chinese Loess. Issue 8 (21st April 2023) - Zhou, Weijian; Kong, Xianghui; Du, Yajuan; Xie, Xingjun; Xian, Feng; Tang, Ling; Zhou, Jie; Zhao, Guoqing; Fu, Yunchong; Chen, Ning
Abstract: The Matuyama‐Gauss (M‐G) magnetic polarity reversal is regarded as a fundamental time marker in the stratigraphic division of the Quaternary‐Neogene. However, previous paleomagnetic studies have shown that the M‐G is mainly recorded in the Chinese loess unit L33 —a glacial stage (corresponding to marine isotope stage 104, i.e., MIS 104)—which is asynchronous with the timing recorded in marine sediments. Here, we solve this long‐standing debate by exploiting a method to extract reproducible records of paleomagnetic field intensity from Xifeng and Lantian loess profiles with meteoric 10 Be. The results showed that for both loess profiles, the 10 Be‐derived M‐G boundary is located in paleosol S32 ca. 2, 589 ± 3 ka, which corresponds to MIS 103. This is synchronous with that seen in marine sediments, though it is, on average, ∼19 ka younger than the boundary inferred from paleomagnetic measurements from the two profiles, which demonstrates that magnetic overprinting has occurred. Plain Language Summary: The Matuyama‐Gauss (M‐G) geomagnetic polarity boundary that occurred at ∼2.6 Ma is usually considered as the key time marker for the division of Quaternary‐Neogene strata because it is globally synchronous. However, previous paleomagnetic studies have indicated that the M‐G boundary is asynchronous between the Chinese loess and marine sediments. This will undoubtedly lead to uncertainties in loess chronology frameworks based on the timing of paleomagnetic polarity reversals and their paleoclimate correlations with global records. To our knowledge, this study is the first to use 10 Be‐a proxy for global average paleomagnetic field intensity to trace the M‐G boundary from two loess profiles. We found that the exact positions of the M‐G boundary in both profiles were recorded in S32, which corresponds to MIS 103, indicating that they are synchronous with marine sediment records. Key Points: The loess 10 Be‐derived M‐G boundary is located in paleosol S32 (corresponding to MIS 103), consistent with marine sediment records The age of the 10 Be‐derived M‐G boundary is ∼19 ka younger than the age of paleomagnetic measurements in the same loess sediments The primary magnetic remanence obtained during the M‐G polarity reversal was overprinted by later superimposed magnetic signals